Public debt in the East of Eden - how does the euro serve the sustainability of public finances? - Deák, Veronika; Novák, Zsuzsanna (Public Finance Quarterly, 2024)
Overall, European countries’ public debt has beneﬁted from the inﬂationary developments of recent quarters, mitigating the negative impact of previous overspending on ﬁscal balances. In this paper, we investigate the basic economic-statistical relationships underlying the debt accumulation since 2008 using linear panel regression estimates. Drawing on the ﬁndings of the literature exploring regional processes, the analysis focuses on the Central and Eastern European and Baltic countries, but extends the assessment of the determinants of public debt dynamics to the European Union as a whole. While the study points to the contradictory role of the common monetary policy in relation to a sustainable debt path, it also demonstrates that debt management is primarily the responsibility of domestic economic policy and cannot be shifted to the European level authorities.